Best Interests Assessor Role: An Opportunity or a 'Dead End' for Adult Social Workers?. Issue 2 (15th March 2018) - Hubbard, Rachel
Abstract : This opinion article explores the significance of the Best Interests Assessor role in England and Wales for social workers working with adults. It considers the challenges of the role following the Supreme Court's Cheshire West (2014) judgement and the implications for BIAs of the Law Commission's 2017 plans for replacing DoLS with the 'Liberty Protection Safeguards'. The author explains why they consider the BIA role to be a valuable one for the status of adult social work as well as for people who may lack capacity to uphold their human rights, with some reservations about the risk of diluting the safeguards the current role represents for those vulnerable people.